1984
DOI: 10.1042/bj2180987
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of hepatic nuclear DNA in rats fed with a carcinogenic methyl-deficient diet

Abstract: A progressive decrease was observed in the 5-methyldeoxycytidine content of hepatic DNA in male F344 rats fed with a hepatocarcinogenic methyl-deficient diet. The same dietary regimen resulted in altered hepatic contents of S-adenosylmethionine, the methyl-donating species, and S-adenosylhomocysteine, an inhibitor of DNA methylase. The data indicate that this carcinogenic dietary manipulation is sufficient to alter a possible regulatory process, DNA methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(75 citation statements)
references
References 22 publications
(25 reference statements)
3
69
0
3
Order By: Relevance
“…For example, rats fed a diet deficient in methionine and choline exhibited a change from normal DNA methylation to global DNA hypomethylation that included specific gene hypomethylation (94,95). A folate-deficient diet introduced to healthy rats led to DNA hypomethylation in the brain (96).…”
Section: Dietary Folate and Dna Methylationmentioning
confidence: 99%
“…For example, rats fed a diet deficient in methionine and choline exhibited a change from normal DNA methylation to global DNA hypomethylation that included specific gene hypomethylation (94,95). A folate-deficient diet introduced to healthy rats led to DNA hypomethylation in the brain (96).…”
Section: Dietary Folate and Dna Methylationmentioning
confidence: 99%
“…Animals fed diets deficient in methyl donors (choline and methionine) have hypomethylated DNA [49][50][51]. These deficiencies have been shown to cause both global [52] and gene-specific hypomethylation [53]. However, research has focused on the carcinogenic effects of methyl-deficient diets; e.g.…”
Section: Animal Studiesmentioning
confidence: 99%
“…DNA methylation is a major epigenetic mechanism that mediates genomic imprinting and X-chromosome inactivation and regulates tissue-specific gene expression, cell differentiation, and chromatin structure (20,21). The reported effects of choline or methyl group deficiency on global DNA methylation vary; most authors observed hypomethylation (22)(23)(24)(25)(26)(27)(28)(29), some no change (30), and some hypermethylation (31,32), suggesting that DNA methylation may respond to the supply of methyl groups in a complex fashion that includes alterations in the activities of DNA methylating and/or demethylating enzymes. DNA methylation patterns acquired during development may be inherited through the cell divisions in a process catalyzed by DNA methyltransferase 1 (DNMT1) that methylates hemimethylated CpG sites and, thus, restores the parental methylation pattern on the daughter DNA strand after DNA replication (33).…”
mentioning
confidence: 99%